Factors Affecting the Takers of the Qualifying Examinations as Part of the Accountancy Program Retention Policy: The Case of a University in Central Luzon Philippines - Salcedo, Arnold; Pamintuan, Jon Bryan B.; Malit, Ronaldo P.; Cruz, Amelito C. Dela; Balingit, Edgardo P. (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
This research was carried out to assess the qualifying examinations being administered by a school’s department for a of university in Central Luzon, Philippines for the Incoming Second Year, Third Year and Fifth Year BS Accountancy Students. Using the physical and administrative factors are from Aiken et al. (2008), and the Psychological Testing and Assessment, and University of Waterloo’s Center for Excellence (2016), when Preparing Tests and Exams are the guidelines for qualitative factors of exams revealed that the quality of exams had the lowest mean rating compared to physical environment and administrative responsibilities as the factors when assessing the qualifying examinations. The participants were two hundred ninety four (294) students who took the qualifying examinations. The analysis of variance findings confirmed that there is a significant difference on the assessment of the qualifying exams if grouped according to incoming year level and status. The return of the two strike policy to replace the one strike policy, is the most preferred recommendation by the examinees followed by the special remediation program for deserving ‘late bloomer’ students and the special review classes in preparation of the examination.